Decorative effects and colouring : a lesson with Chris Stott (South Humberside : Chris Stott Videos, 1995)
1. This video covers many different ways of achieving these effects, from simple carving techniques and abrading to grain enhancement and complex colouring, from burning and sandblasting to fuming and chemical dying
Demonstrated by Chris Stott
Keywords: Acrylic painting -- Technique; Interior decoration